Analisis Yuridis Terhadap Pertanggungjawaban Pidana Pada Kasus Korupsi Proyek Studio LPP TVRI Kepulauan Riau - Pratiwi, Kekeh Intan; Bangun, Anza Ronaza (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines criminal liability in the corruption case of the LPP TVRI Riau Islands Studio Development Project, which involved three defendants with sentences ranging from 1.6 to 6 years in prison. This case is an important representation in understanding how law enforcement officers apply the elements of criminal acts of corruption as stipulated in Law Number 31 of 1999 in conjunction with Law Number 20 of 2001. The focus of the research is directed at the legal construction related to proving the elements of enriching oneself or others, the existence of unlawful acts, and the occurrence of state losses based on the calculations of state auditors. Through a normative legal approach by examining court decisions, related regulations, and academic literature, this study found that the judge considered the role of each defendant, from planning, budgeting, to project implementation. Criminal liability was established based on the level of involvement, intent, and abuse of authority proven during the trial process. In addition, the decision demonstrates the consistent application of the mens rea and actus reus doctrines in criminal law on corruption, while also reflecting preventive efforts to strengthen the governance of public broadcasting institutions. The research findings indicate that criminal liability is determined not only by position but also by active contribution to the occurrence of state losses. This research emphasizes the importance of improving the internal oversight system of broadcasting institutions to prevent similar corrupt practices. Therefore, this legal analysis provides a comprehensive overview of the application of law in regional corruption cases and its relevance to national law enforcement.